From Service Quality to Student Experience: A Bibliometric Analysis of Service Quality Research in Higher Education - Arief, Aditya Ferdiana; Nuryanto; Mardiana, Tri; Setiawan, Abdul Yani (Sunan Kalijaga International Journal on Islamic Educational Research, 2026)
This study maps the intellectual landscape of service quality research in higher education and traces its shift from a classical service evaluation orientation toward an ecosystem increasingly centered on student experience and digital transformation. A bibliometric analysis was conducted on Scopus metadata related to service quality and higher education. The dataset included 1,887 documents from 770 sources and was analyzed using bibliometrix and Biblioshiny in R Studio. The analysis covered scientific production, citations, publication sources, authors, affiliations, countries, and conceptual mapping through keywords, trend topics, co-word networks, thematic maps, and factorial analysis. The field has developed as an increasingly collaborative and multidisciplinary domain, with strong contributions from Asia, especially India with 145 documents, China with 141, Indonesia with 137, and Malaysia with 105. The most dominant keywords are higher education with 1,092 occurrences and service quality with 904, followed by students with 141 and student satisfaction with 131. Conceptually, the field has shifted from classical service quality evaluation toward student experience, system quality, information quality, e-learning, and increasingly hybrid educational services. Emerging themes such as artificial intelligence, ChatGPT, trust, and student well-being have appeared, but remain fragmented